Kafka in light of the accident - Caygill, Howard 20./21. Jh (Bloomsbury Academic, 2017)
"By challenging many of the assumptions, misguided presuppositions and even legends that have surrounded the legacy and reception of Franz Kafka's work during the 20th century, Howard Caygill provides us with a radical new way of reading Kafka. He advances a unique philosophical interpretation via the pivotal theme of the accident, understood both philosophically and in a broader cultural context, that includes the philosophical and sociological basis of accident insurance and the understanding of the concepts of chance and necessity. Caygill reveals how Kafka's reception was governed by a series of accidents - from the order of Max Brod's posthumous publication of the novels and the correction of 'misprints', to many other posthumous editorial strategies. The focus on the accident casts light on the role of media in Kafka's work, particularly visual media and above all photography. By stressing the role of contingency in his authorship, Caygill also fundamentally questions the 20th century view of Kafka's work as 'kafkaesque'. Instead of a narration of domination, Caygill argues that Kafka's work is best read as a narration of defiance, one which affirms (often comically) the role of error and contingency in historical struggle. Kafka's defiance is situated within early 20th century radical culture, with particular emphasis lent to the roles of radical Judaism, the European socialist and feminist movements, and the subaltern histories of the United States and China."--Page [4] of cover
Keywords: Kafka, Franz -- 1883-1924; Kafka, Franz / 1883-1924 / Criticism and interpretation; Contingency (Philosophy); Kafka, Franz / 1883-1924; Criticism, interpretation, etc